2012
DOI: 10.1093/icvts/ivs053
|View full text |Cite
|
Sign up to set email alerts
|

Ablation for atrial fibrillation during mitral valve surgery: 1-year results through continuous subcutaneous monitoring

Abstract: Continuous monitoring of cardiac rhythm may play an important role in measuring the true symptomatic/asymptomatic atrial fibrillation (AF) burden and improve the management of anti-arrhythmic and anti-thrombotic therapies. Forty-seven patients with mitral valve disease and longstanding persistent AF (LSPAF) underwent a left atrial maze procedure with bipolar radiofrequency and valve surgery. The follow-up data recorded by an implanted loop recorder were analysed after 3, 6 and 12 months. On discharge, 40 (85.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
1
11
0
3
Order By: Relevance
“…As compared with long-term monitoring, spot ECG recordings tend to overestimate success by approximately 12 percentage points. 25 A study that used continuous monitoring with an implantable loop recorder after ablation in patients with long-standing persistent atrial fibrillation showed a success rate of 65% at 1 year, 26 a finding very similar to that of our trial.…”
Section: Discussionsupporting
confidence: 86%
“…As compared with long-term monitoring, spot ECG recordings tend to overestimate success by approximately 12 percentage points. 25 A study that used continuous monitoring with an implantable loop recorder after ablation in patients with long-standing persistent atrial fibrillation showed a success rate of 65% at 1 year, 26 a finding very similar to that of our trial.…”
Section: Discussionsupporting
confidence: 86%
“…With regard to the rhythm assessment via electrocardiography (ECG) monitoring, office ECG and 24-h Holter monitoring are commonly used to assess cardiac rhythm after the ablation procedure, but they have limited abilities to detect AF paroxysmal recurrences [10,11]. Continuous and precise rhythm monitoring may help clinicians uncover the true incidence and duration of AF and assess the efficacy of different AF ablation techniques during mitral valve surgery [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Ip and co-workers report that in about 45 AF patients, who underwent video-assisted epicardial ablation and ICM implantation; as many as 46 % of the AF recurrences were asymptomatic, whereas only 66 % of the symptomatic episodes were AF-related. 27 Bogachev-Prokophiev et al 28 reported ablation results for AF with mitral valve surgery after one year of continuous monitoring. If an ICM is implanted for a period before the procedure, this may help the assessment of AF behaviour and improve patient management.…”
Section: The Role Of Monitoring In Rhythm Control Strategiesmentioning
confidence: 99%